"Where do I go? Who do I go to?": BRCA Previvors, genetic counselors and family planning - Mariah L. Wellman; Avery E. Holton; Kimberly A. Kaphingst (Elsevier, 2023)
Objective: We sought to understand BRCA previvors' perceptions of communication with genetic counselors and other healthcare providers. Methods: We conducted 16 qualitative interviews and utilized thematic analysis to develop patterns present in the narratives of previvors. Results: Interviews with previvors suggest genetic counselors and other providers often make assumptions about previvors' family planning and treatment needs based on perceived gender, age, and sexual orientation. Conclusion: BRCA patients require individualized attention when planning for their future and making healthcare decisions and we argue that implementing patient-centered care practices into the communication process can provide a higher quality of care. Innovation: This study offers an innovative lens through which scholars and healthcare providers may examine the experiences of BRCA previvors as they seek adequate care. Asking previvors to explain their perceptions of conversations with genetic counselors and healthcare providers offers insight into the communicative process of seeking care rather than the health outcomes of the care itself. Our findings suggest biases among providers related to gender, age, and sexual orientation are concerning elements of family planning communication that potentially interrupt previvors' abilities to express their care needs in a safe environment. We argue for an increased awareness of, and advocacy for, more inclusive conversations regarding treatment and family planning decisions.